Hanoverian F/W‐line contributes to segregation of Warmblood fragile foal syndrome type 1 variant PLOD1:c.2032G>A in Warmblood horses. (19th May 2020) - Metzger, Julia; Kreft, Oliver; Sieme, Harald; Martinsson, Gunilla; Reineking, Wencke; Hewicker‐Trautwein, Marion; Distl, Ottmar
Abstract: Background: Warmblood fragile foal syndrome (WFFS) is a lethal condition detected in Warmblood horses. Its origin and association with performance traits and fertility among horse populations is unknown. Objectives: To validate the previously identified WFFS type 1 (WFFST1)‐associated missense variant PLOD1: c.2032G>A and to investigate its distribution among various horses with particular focus on Hanoverian breed, as well as its pathomorphological picture. The study aimed at identifying the origin of the mutant allele and its correlation with performance and fertility traits in Warmblood horses. Study design: Retrospective case‐control and association study. Methods: WFFST1 variant was validated using whole genome sequencing (WGS) in 78 equids. In an affected foal with a homozygous mutant genotype, necropsy was performed. Skin samples were examined using histology and transmission electron microscopy. Pathway analysis was performed to trace back 81 genetic carriers to the most common recent ancestor. Furthermore, generalised linear model analysis was employed to test estimated breeding values (EBVs) for differences in performance and fertility traits among different genotypes in Hanoverian horses. Results: WFFST1 variant had the lowest minor allele frequency among all variants detected in WGS data in the region of PLOD1 . Further genotyping of this variant revealed allele frequencies of 0.14 in Hanoverian horses. Histological investigations of the WFFST1‐affected foal showed loosely arranged collagen fibres in the dermis. Ultrastructurally, multifocal areas with degraded collagen fibrils and fibrillar plaques were detected. Further pathway analysis revealed a stallion from the Hanoverian sire F/W line as the most common recent ancestor of all tested genetic carriers. Furthermore, WFFST1 variant was found to be correlated with EBVs for gait‐related traits as well as conformation and dressage. Main limitations: Study evaluated carriers and cases only from Europe. Conclusions: This study provides a comprehensive evaluation of WFFST1 variant and traces it back to its potential origin.